Intumescent flame-retardant fabric and preparation method thereof

By applying three synergistic flame retardant coatings on textile fabrics, including phosphorus-nitrogen-doped graphene oxide, dendritic polyguanidine/phytic acid@Zn hybrid and acid modified sheet silica gel layer, the The problem of flammability of textile fabrics achieves efficient flame retardant performance and low smoke and low toxic combustion characteristics.

CN119507226APending Publication Date: 2025-02-25SUZHOU YINJIN FLAME RETARDANT NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411415070.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing textile fabrics are flammable and spread rapidly when burning, threatening life and property safety.

Method used

The synergistic effect of three-layer flame retardant coatings, including phosphorus-nitrogen-doped graphene oxide, dendritic polyguanidine/phytic acid@Zn hybrid and acidified modified sheet silica gel layer, isolating the contact between the fire source and the fabric , achieve flame retardant performance.

Benefits of technology

The rapid expansion of the expansion flame retardant forms a carbon layer to isolate the fire source, significantly improve the flame retardant performance of the fabric, reduce fire hazards, and generate a small amount of smoke during the combustion process to release harmless gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079194110000151
    Figure BDA0005079194110000151
  • Figure HDA0005079194140000011
    Figure HDA0005079194140000011
Patent Text Reader

Abstract

The invention provides an intumescent flame-retardant fabric which comprises a fabric layer, an adhesive layer containing phosphorus and nitrogen doped graphene oxide, an adhesive layer containing dendritic polyguanidine / phytic acid Zn heterozygote and an adhesive layer containing acidified modified flaky silicon dioxide, the fabric layer, the adhesive layer containing phosphorus and nitrogen doped graphene oxide, the adhesive layer containing dendritic polyguanidine / phytic acid Zn heterozygote and the adhesive layer containing acidized modified flaky silicon dioxide are sequentially compounded to obtain the flame-retardant fabric, the intumescent flame-retardant method is adopted, the contact between a fire source and the fabric layer is isolated by utilizing the synergistic effect of the three flame-retardant coating layers, and the flame-retardant effect is achieved. Therefore, the fabric is endowed with flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textile fabrics, and in particular to an expanded flame-retardant fabric and a preparation method thereof. Background Art

[0002] ]In recent years, with the rapid development of my country's economy and science and technology, people's functional requirements for textile fabrics have been continuously improved. However, most of the current textile fabrics are flammable or flammable fabrics. Once burned, they will spread rapidly, posing a major threat to people's lives and property safety. The preparation of existing flame-retardant fabrics mainly includes copolymerization, blending, composite spinning flame-retardant modification and finishing methods. Among them, the finishing method has less restrictions on the thermal stability of flame-retardant additives and the size of condensed particles, and has the advantages of simple process and low cost, which can meet different degrees of flame-retardant requirements. At present, intumescent flame retardants can quickly expand to form a layer of carbon layer when encountering fire, isolating the contact between the fire source and the fabric, and then giving the fabric flame retardant properties. Compared with traditional flame retardants, intumescent flame retardants have the characteristics of high efficiency, low smoke and low toxicity. They produce less smoke and do not release harmful gases during the combustion process, which can significantly reduce the hazards of fire. Summary of the invention

[0003] Technical problem to be solved: The present invention aims to provide an intumescent flame-retardant fabric, which adopts an intumescent flame-retardant method and utilizes the synergistic effect between three layers of flame-retardant coating to isolate the contact between the fire source and the fabric layer, thereby giving the fabric flame-retardant properties.

[0004] Technical solution: Disclosed is an intumescent flame-retardant fabric, comprising a fabric layer, an adhesive layer containing phosphorus-nitrogen doped graphene oxide, an adhesive layer containing a dendritic polyguanidine / phytic acid@Zn hybrid, and an adhesive layer containing acid-modified flaky silica. The fabric layer, the adhesive layer containing phosphorus-nitrogen doped graphene oxide, the adhesive layer containing a dendritic polyguanidine / phytic acid@Zn hybrid, and the adhesive layer containing acid-modified flaky silica are compounded in sequence to obtain a flame-retardant fabric. Preferably, the method for preparing phosphorus-nitrogen doped graphene oxide comprises the following steps: S1-1. Graphene oxide is added to water and ultrasonically dispersed to form a suspension having a concentration of 1 to 4 mg / mL; S1-2. A nitrogen source is added to the suspension and magnetically stirred to obtain a mixed solution, the mixed solution is reacted at 160-200° C. for 3-6 hours, cooled to room temperature, and then freeze-dried to obtain nitrogen-doped graphene oxide; S1-3. Add a 10-15 wt% hypophosphorous acid solution to a 1-5 mg / mL nitrogen-doped graphene oxide suspension and react at 180-300° C. for 1-2 h to obtain phosphorus-nitrogen doped graphene oxide. Preferably, the nitrogen source is one or more of hydrazine hydrate, ethylenediamine, and urea, the mass ratio of graphene oxide and nitrogen source is 1-13:1-45, and the volume ratio of hypophosphorous acid solution and nitrogen-doped graphene oxide suspension is 3-20:4-60. Preferably, the preparation method of the dendritic polyguanidine / phytic acid@Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate is 1 to 3: 2 to 5, and the volume ratio is 1 to 3: 20 to 35. The polyguanidine / aqueous solution is stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1 to 2:1 to 4 to zinc nitrate to the above solution, and react at 0 to 15°C for 8 to 12 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Preferably, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. Disperse graphene oxide in DMF and ultrasonicate for 0.5 to 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 1 to 3:1 to 5:0.005 to 0.008 to graphene oxide are added to the suspension and stirred, followed by an oil bath reaction at 55 to 70°C for 20 to 30 hours; S3-3. The product obtained in S3-2 is centrifuged at high speed, the lower layer of solid product is taken out, added to DMF, and centrifuged and washed for 0.5 to 1 hour; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. After washing and drying the product obtained in S3-4, heat treatment is carried out in air at 700-800°C for 10-15 hours to obtain flaky silica. S3-6. Diethylphosphoethyltriethoxysilane is dissolved in an acetone / acetic acid solution with a volume ratio of 20:1, and then the flaky silica is added and reacted at 80-160°C for 0.5-1.5 hours to obtain acid-modified flaky silica. Preferably, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silicon dioxide in S3-6 is 1-5:95-99. Preferably, the method for preparing the intumescent flame-retardant fabric comprises the following steps: S1. Add the acid source to the water and stir evenly, then add the carbon source, gas source, binder and cross-linking agent and continue stirring to obtain a glue layer solution; S2. The phosphorus-nitrogen doped graphene oxide and the acid-modified flaky silica were added to the adhesive layer solution obtained in S3-1 and stirred thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. The dendritic polyguanidine / PA @ Zn hybrid was added to the polyurethane solution and stirred thoroughly to obtain a dendritic polyguanidine / PA @ Zn hybrid gel layer; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and after each coating, the adhesive layer is double-dipped and double-rolled to prepare the intumescent flame-retardant fabric. Preferably, the acid source is ammonium polyphosphate, the carbon source is one or both of pentaerythritol and dipentaerythritol, the gas source is one or both of melamine and dicyandiamide, the binder is one or both of polyurethane and acrylate, the cross-linking agent is glutaraldehyde, the mass ratio of the acid source, the carbon source, the gas source and phosphorus-nitrogen doped graphene oxide is 21-28:7-9:2-4:2-3, the mass ratio of the acid source, the carbon source, the gas source and the acid-modified flaky silica is 21-38:7-9:2-4:2-3, the mass ratio of the binder to the cross-linking agent is 6-8:2-5, and the mass ratio of the branched polyguanidine / PA@Zn hybrid to the polyurethane is 1-3:7-9. Preferably, in the two-dipping and two-rolling process in S4, the pre-baking temperature is 70-95° C., the time is 120-180 seconds, and the baking temperature is 150-180° C., and the time is 160-280 seconds. Beneficial effects: 1. The phosphorus-nitrogen doped graphene oxide prepared in the present invention expands when the nitrogen element burns, releasing ammonia to dilute the concentration of oxygen and combustible volatiles, and the phosphorus element promotes the cross-linking of the carbon element to form a carbon layer to prevent the combustion; 2. The dendritic polyguanidine / PA@Zn hybrid of the present invention has a high surface area, which enables it to capture and disperse heat more effectively during combustion. 2+ The introduction of promotes more cracked organic matter to be converted into carbon, which is converted into ZnO during the combustion process and diffuses in the residual carbon, effectively improving the strength of the residual carbon and its barrier effect on flames and smoke; 3. The phosphoric acid small molecules produced when the phytic acid introduced in the present invention is burned can form PN compounds with the nitrogen-containing groups in the polyguanidine at high temperature, thereby enhancing the self-carbon forming ability of the polyguanidine. The complexation of zinc metal ions with phytic acid can promote the conversion of the organic resin matrix into more carbon residues at a lower temperature, thereby more effectively protecting the fabric from high temperature damage; 4. The acid-modified flaky silica prepared in the present invention has acidic sites, which absorb NH 3 At the same time, it can promote the cross-linking and esterification reaction of ammonium polyphosphate, thereby inhibiting the competition between phosphorus and silicon elements and oxygen, preferentially combining with carbon elements to inhibit fabric oxidation, and helping to form a dense carbon layer during the combustion process; 5. In the present invention, during combustion, the phosphorus-nitrogen doped graphene oxide glue layer releases ammonia to dilute the combustible gas, the branched polyguanidine / phytic acid@Zn hybrid glue layer generates ZnO embedded in the carbon layer to enhance the strength of the carbon layer and provide heat insulation, and the acidified modified flaky silica gel layer absorbs excess NH 3 And form a dense carbon layer to isolate oxygen. The three layers of coating have a synergistic effect, thus giving the fabric flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is the flame retardant performance retention rate of each sample in the present invention after washing 4 times. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water, stir well, add pentaerythritol, melamine, polyurethane and glutaraldehyde, the mass ratio of polyurethane to glutaraldehyde is 6:2, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, respectively, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine in S1 to phosphorus-nitrogen doped graphene oxide in S2 is 21:7:4:2, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine in S1 to acid-modified flaky silica in S2 is 21:7:4:2, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 1:7, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 70°C for 120s and then baked at 150°C for 160s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension having a concentration of 1 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 1:1 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 160° C. for 3 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Add hypophosphorous acid to a nitrogen-doped graphene oxide suspension having a concentration of 1 mg / mL, wherein the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 3:4, and react at 180° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; The preparation method of the dendritic polyguanidine / phytic acid@Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 1:2 was added to the volume ratio of 1:20 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1:1 to zinc nitrate to the above solution, and react at 0°C for 8h to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 0.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 1:1:0.005 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 55°C for 20h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 0.5h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 700°C for 10h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 1:95, and react at 80°C for 0.5h to obtain acid-modified flaky silica. Example 2 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well, then add pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 8:5, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 28:9:4:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 28:9:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 3:9, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 95°C for 180s and then baked at 180°C for 280s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension having a concentration of 4 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 13:1 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 200° C. for 6 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Adding 15 wt% hypophosphorous acid to a 5 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 20:60, and reacting at 300 ° C for 2 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 3:5 was added to the volume ratio of 3:35 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 2:4 to zinc nitrate to the above solution, and react at 15°C for 12 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 3:5:0.008 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 70°C for 30h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 800°C for 15h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 5:99, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Example 3 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well, then add pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 6:5, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 26:8:3:2, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 28:9:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 2:9, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric. After each coating, the fabric is pre-baked at 85°C for 180s and then baked at 160°C for 250s to prepare the intumescent flame-retardant fabric. The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 2 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 10:45 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 200° C. for 6 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Add 15wt% hypophosphorous acid to 5mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of hypophosphorous acid solution to nitrogen-doped graphene oxide suspension is 13:60, and react at 280°C for 1h to obtain phosphorus-nitrogen-doped graphene oxide. The preparation method of the branched polyguanidine / phytic acid@Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 2:35 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1.5:4 to zinc nitrate to the above solution, and react at 10°C for 10 hours to obtain a dendritic polyguanidine / PA@Zn hybrid. Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 3:5:0.008 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 70°C for 30h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 800°C for 15h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 5:99, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Example 4 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water, stir well, add pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 7:4, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 26:8:3:2, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 28:9:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 2:9, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 85°C for 180s and then baked at 160°C for 250s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 3 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 3:45 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 190° C. for 4 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Adding 12 wt% hypophosphorous acid to a 3 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 11:60, and reacting at 260° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 3:4 was added to the volume ratio of 2:35 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1.5:4 to zinc nitrate to the above solution, and react at 10°C for 10 hours to obtain a dendritic polyguanidine / PA@Zn hybrid. Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 3:5:0.008 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 70°C for 30h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 800°C for 15h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 5:99, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Example 5 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well, then add pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 7:5, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 21:8:3:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 28:8:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 2:9, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 80°C for 180s and then baked at 180°C for 280s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 2 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 13:45 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 190° C. for 4.5 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Adding 11 wt% hypophosphorous acid to a 3 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 17:60, and reacting at 230° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 2:27 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1:4 to zinc nitrate to the above solution, and react at 5°C for 9 hours to obtain a dendritic polyguanidine / PA@Zn hybrid. Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 3:5:0.008 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 70°C for 30h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 750°C for 12h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 4:99, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Example 6 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water, stir well, add pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 7:3, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 28:9:4:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 28:9:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 2:7, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 75°C for 170s and then baked at 175°C for 200s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 2 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 10:43 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 160° C. for 4 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Adding 11 wt% hypophosphorous acid to a 2 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 15:27, and reacting at 290° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 13:35 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 2:4 to zinc nitrate to the above solution, and react at 15°C for 12 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 3:5:0.008 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 70°C for 30h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 800°C for 15h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 5:99, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Example 7 A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well before adding pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 6:5, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 23:8:3:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 25:8:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 3:8, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 80°C for 180s and then baked at 180°C for 280s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 2 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 8:45 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 180° C. for 4.5 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Add 10 wt% hypophosphorous acid to a 3 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 17:58, and react at 250° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 3:34 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 2:3 to zinc nitrate to the above solution, and react at 12°C for 10 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 2:5:0.006 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 60°C for 28h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 750°C for 11h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 4:89, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Comparative Example 1 The difference between this comparative example and Example 7 is that only the flame retardant coating composed of ammonium polyphosphate, pentaerythritol, melamine, glutaraldehyde, polyurethane and glutaraldehyde in a mass ratio of 23:8:3:6:5 is coated on the surface of the fabric. Comparative Example 2 The difference between this comparative example and Example 7 is that only the phosphorus-nitrogen doped graphene oxide glue layer is coated. Comparative Example 3 The difference between this comparative example and Example 7 is that only the acidified modified flaky silica gel layer is coated. Comparative Example 4 The difference between this comparative example and Example 7 is that the adhesive layer containing phosphorus-nitrogen doped graphene oxide and the adhesive layer containing acid-modified flaky silicon dioxide are coated in sequence. Comparative Example 5 The difference between this comparative example and Example 7 is that the adhesive layer containing the dendritic polyguanidine / phytic acid@Zn hybrid and the adhesive layer containing phosphorus and nitrogen doped graphene oxide are coated in sequence. Comparative Example 6 The difference between this comparative example and Example 7 is that the gel layer containing the dendritic polyguanidine / phytic acid@Zn hybrid and the gel layer containing the acidified modified flaky silica gel are coated in sequence. Comparative Example 7 The difference between this comparative example and Example 7 is that the graphene oxide is not modified. A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well before adding pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 6:5, and continue stirring to obtain a glue layer solution; S2. adding graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, respectively, wherein the mass ratio of ammonium polyphosphate, pentaerythritol, melamine and phosphorus-nitrogen doped graphene oxide is 23:8:3:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine and acid-modified flaky silica is 25:8:4:3, and stirring thoroughly to obtain an adhesive layer containing graphene oxide and a silica gel layer containing acid-modified flaky silica; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 3:8, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 80°C for 180s and then baked at 180°C for 280s to prepare an intumescent flame-retardant fabric; The preparation method of the dendritic polyguanidine / phytic acid@Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 3:34 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 2:3 to zinc nitrate to the above solution, and react at 12°C for 10 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 2:5:0.006 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 60°C for 28h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. The product obtained in S3-4 was washed and dried, and then heat treated in air at 750°C for 11h to obtain flaky silica; S3-6. Dissolve diethylphosphoethyltriethoxysilane in an acetone / acetic acid solution with a volume ratio of 20:1, then add flaky silica, the mass ratio of diethylphosphoethyltriethoxysilane to flaky silica is 4:89, and react at 160°C for 1.5h to obtain acid-modified flaky silica. Comparative Example 8 The difference between this comparative example and Example 7 is that the flaky silicon dioxide is not modified. A method for preparing an intumescent flame-retardant fabric comprises the following steps: S1. Add ammonium polyphosphate to water and stir well before adding pentaerythritol, melamine, polyurethane and glutaraldehyde in a mass ratio of 6:5, and continue stirring to obtain a glue layer solution; S2. Adding phosphorus-nitrogen doped graphene oxide and acid-modified flaky silica to the adhesive layer solution obtained in S1, the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to phosphorus-nitrogen doped graphene oxide is 23:8:3:3, and the mass ratio of ammonium polyphosphate, pentaerythritol, melamine to acid-modified flaky silica is 25:8:4:3, and stirring thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. Add the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution and stir thoroughly, the mass ratio of the dendritic polyguanidine / PA@Zn hybrid to the polyurethane solution is 3:8, and a dendritic polyguanidine / PA@Zn hybrid adhesive layer is obtained; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and each coating is pre-baked at 80°C for 180s and then baked at 180°C for 280s to prepare an intumescent flame-retardant fabric; The method for preparing phosphorus-nitrogen-doped graphene oxide comprises the following steps: S1-1. Graphene oxide was added to water and ultrasonically dispersed to form a suspension with a concentration of 2 mg / mL; S1-2. Add hydrazine hydrate in a mass ratio of 8:45 to graphene oxide to the suspension and stir magnetically to obtain a mixed solution. The mixed solution is reacted at 180° C. for 4.5 h and then cooled to room temperature and freeze-dried to obtain nitrogen-doped graphene oxide. S1-3. Add 10 wt% hypophosphorous acid to a 3 mg / mL nitrogen-doped graphene oxide suspension, the volume ratio of the hypophosphorous acid solution to the nitrogen-doped graphene oxide suspension is 17:58, and react at 250° C. for 1 h to obtain phosphorus-nitrogen-doped graphene oxide; wherein the preparation method of the branched polyguanidine / phytic acid @ Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate was 2:5 was added to the volume ratio of 3:34 polyguanidine / water solution, and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 2:3 to zinc nitrate to the above solution, and react at 12°C for 10 hours to obtain a dendritic polyguanidine / PA@Zn hybrid; Wherein, the preparation of the flaky silicon dioxide comprises the following steps: S3-1. The graphene oxide was dispersed in DMF and ultrasonicated for 1 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 2:5:0.006 to graphene oxide were added to the suspension and stirred, and then reacted in an oil bath at 60°C for 28h; S3-3. The product obtained from S3-2 was centrifuged at high speed and the solid product was added to DMF and centrifuged and washed for 1h; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. After washing and drying the product obtained in S3-4, heat treatment was performed at 750°C in air for 11 hours to obtain flaky silicon dioxide. Performance Testing The flame retardant properties of the samples prepared in Examples 1-7 and Comparative Examples 1-8 of the present invention were tested, and the results are shown in Table 1. Table 1 LOI value and UL-94 results of intumescent flame retardant fabrics LOI(%) UL-94 <![CDATA[T 1 (s)]]> <![CDATA[T 2 (s)]]> Example 1 32.0 V-0 1.1 0.9 Example 2 31.7 V-0 1.6 0.9 Example 3 30.7 V-0 1.5 0.8 Example 4 30.8 V-0 2.3 1.1 Example 5 32.5 V-0 1.9 1.0 Example 6 30.7 V-0 1.4 0.8 Example 7 33.5 V-0 1.1 0.6 Comparative Example 1 22.3 V-2 6.2 2.3 Comparative Example 2 27.5 V-1 5.8 1.8 Comparative Example 3 26.8 V-1 6.0 1.6 Comparative Example 4 28.9 V-1 5.7 2.1 Comparative Example 5 27.6 V-1 5.8 1.9 Comparative Example 6 26.9 V-1 5.9 2.1 Comparative Example 7 29.1 V-1 6.1 2.2 Comparative Example 8 29.5 V-1 6.3 2.4 Note: 1. LOI test: Tested on a COI indexer according to ASTM D2863 standard, LOI < 22% is flammable, LOI 22-27% is flammable, LOI 27-34% is difficult to burn, LOI > 34% is non-flammable; 2. Vertical combustion analysis: Tested according to ASTM D3801 standard, UL-94 results are classified by combustion grade V-0, V-1 or V-2, and the V-0 grade indicates the polymer material with the best flame retardancy; 3.T 1 Refers to the flaming burning time after the first application of flame, T 2 Refers to the flaming burning time after the second application of flame. Table 2 Effect of washing times on flame retardant properties Note: The finished fabrics are washed according to the method of BS5651-1978. The specific method is: add 5g / L household laundry detergent, the mass ratio of washed fabric to detergent is 1:10, the washing temperature is 50℃, the washing time is 30min, then rinse with clean water and dry. It can be seen from the table that the LOI value of the flame retardant fabric decreases with the increase of the number of washings. The washing resistance of the traditional intumescent flame retardant fabric in comparative example 1 is poor, and the number of washings can only reach 1 time, which is equivalent to about 5 times of household washing.

Claims

1. An expanded flame-retardant fabric, characterized in that: The intumescent flame-retardant fabric comprises a fabric layer, a glue layer containing phosphorus-nitrogen doped graphene oxide, a glue layer containing a branched polyguanidine / phytic acid@Zn hybrid, and a glue layer containing acid-modified flaky silica. The fabric layer, the glue layer containing phosphorus-nitrogen doped graphene oxide, the glue layer containing a branched polyguanidine / phytic acid@Zn hybrid, and the glue layer containing acid-modified flaky silica are compounded in sequence to obtain a flame-retardant fabric.

2. The expanded flame-retardant fabric according to claim 1, characterized in that: The preparation method of the phosphorus-nitrogen doped graphene oxide comprises the following steps: S1-1. Graphene oxide is added to water and ultrasonically dispersed to form a suspension having a concentration of 1 to 4 mg / mL; S1-2. A nitrogen source is added to the suspension and magnetically stirred to obtain a mixed solution, the mixed solution is reacted at 160-200° C. for 3-6 hours, cooled to room temperature, and then freeze-dried to obtain nitrogen-doped graphene oxide; S1-3. Add a 10-15 wt% hypophosphorous acid solution to a 1-5 mg / mL nitrogen-doped graphene oxide suspension and react at 180-300° C. for 1-2 h to obtain phosphorus-nitrogen doped graphene oxide.

3. The flame retardant polyester fabric according to claim 2, characterized in that: The nitrogen source is one or more of hydrazine hydrate, ethylenediamine and urea, the mass ratio of graphene oxide to the nitrogen source is 1-13:1-45, and the volume ratio of hypophosphorous acid solution to nitrogen-doped graphene oxide suspension is 3-20:4-60.

4. The expanded flame-retardant fabric according to claim 1, characterized in that: The preparation method of the dendritic polyguanidine / phytic acid@Zn hybrid comprises the following steps: S2-1. The mass ratio of phytic acid and zinc nitrate is 1 to 3: 2 to 5, and the volume ratio is 1 to 3: 20 to 35. The polyguanidine / aqueous solution is added and stirred to obtain a homogeneous solution; S2-2. Add ammonium persulfate in a mass ratio of 1-2:1-4 to zinc nitrate to the above solution, and react at 0-15°C for 8-12h to obtain a dendritic polyguanidine / PA@Zn hybrid.

5. The expanded flame-retardant fabric according to claim 1, characterized in that: The preparation of the acid-modified flaky silicon dioxide comprises the following steps: S3-1. Disperse graphene oxide in DMF and ultrasonicate for 0.5 to 1.5 h to obtain a suspension; S3-2. Under nitrogen protection, 3-aminopropyltriethoxysilane and azobisisobutyramidine hydrochloride in a mass ratio of 1 to 3:1 to 5:0.005 to 0.008 to graphene oxide are added to the suspension and stirred, followed by an oil bath reaction at 55 to 70°C for 20 to 30 hours; S3-3. The product obtained in S3-2 is centrifuged at high speed, the lower layer of solid product is taken out, added to DMF, and centrifuged and washed for 0.5 to 1 hour; S3-4. The product obtained in S3-3 was centrifuged and the solid layer was removed and added to 25wt% ammonia water for cross-linking for 24h; S3-5. After washing and drying the product obtained in S3-4, heat treatment is carried out in air at 700-800°C for 10-15 hours to obtain flaky silica. S3-6. Diethylphosphoethyltriethoxysilane is dissolved in an acetone / acetic acid solution with a volume ratio of 20:1, and then the flaky silica is added and reacted at 80-160°C for 0.5-1.5 hours to obtain acid-modified flaky silica.

6. The method for preparing the expanded flame-retardant fabric according to claim 5, characterized in that: The mass ratio of diethylphosphoethyltriethoxysilane to flaky silicon dioxide in the S3-6 is 1-5:95-99.

7. The intumescent flame-retardant fabric according to claim 1, characterized in that: The method for preparing the intumescent flame-retardant fabric comprises the following steps: S1. Add the acid source to the water and stir evenly, then add the carbon source, gas source, binder and cross-linking agent and continue stirring to obtain a glue layer solution; S2. The phosphorus-nitrogen doped graphene oxide and the acid-modified flaky silica were added to the adhesive layer solution obtained in S3-1 and stirred thoroughly to obtain a phosphorus-nitrogen doped graphene oxide adhesive layer and an acid-modified flaky silica silica gel layer; S3. The dendritic polyguanidine / PA @ Zn hybrid was added to the polyurethane solution and stirred thoroughly to obtain a dendritic polyguanidine / PA @ Zn hybrid gel layer; S4. The phosphorus-nitrogen doped graphene oxide adhesive layer, the branched polyguanidine / PA@Zn hybrid adhesive layer and the acid-modified flaky silica gel layer are sequentially coated on the surface of the fabric, and after each coating, the adhesive layer is double-dipped and double-rolled to prepare the intumescent flame-retardant fabric.

8. The method for preparing the expanded flame-retardant fabric according to claim 7, characterized in that: The acid source is ammonium polyphosphate, the carbon source is one or two of pentaerythritol and dipentaerythritol, the gas source is one or two of melamine and dicyandiamide, the binder is one or two of polyurethane and acrylate, the cross-linking agent is glutaraldehyde, the mass ratio of the acid source, the carbon source, the gas source and phosphorus-nitrogen doped graphene oxide is 21-28:7-9:2-4:2-3, the mass ratio of the acid source, the carbon source, the gas source and acid-modified flaky silicon dioxide is 21-38:7-9:2-4:2-3, the mass ratio of the binder to the cross-linking agent is 6-8:2-5, and the mass ratio of the branched polyguanidine / PA@Zn hybrid to polyurethane is 1-3:7-9.

9. The method for preparing the intumescent flame retardant fabric according to claim 7, characterized in that: In the two-dipping and two-rolling process in S4, the pre-baking temperature is 70-95° C., the time is 120-180 seconds, and the baking temperature is 150-180° C., and the time is 160-280 seconds.

Citation Information

Cited By

  • Filler and manufacturing method thereof, resin composition and electronic material using the same

    TWI939267B